2022
DOI: 10.1021/acs.langmuir.2c01891
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting the Leidenfrost Temperature of Droplets via Nanobubble Dispersion

Abstract: Droplets may rebound/levitate when deposited over a hot substrate (beyond a critical temperature) due to the formation of a stable vapor microcushion between the droplet and the substrate. This is known as the Leidenfrost phenomenon. In this article, we experimentally allow droplets to impact the hot surface with a certain velocity, and the temperature at which droplets show the onset of rebound with minimal spraying is known as the dynamic Leidenfrost temperature (T DL ). Here we propose and validate a novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…In this case, the droplet rises above its vapor cushion, which acts as a thermal insulator. Therefore, the droplet exists on the superheated surface for more than 300 s without instantaneous evaporation, which is well-known as the Leidenfrost effect. , The Leidenfrost temperature above which the droplet begins to levitate and droplet dynamics depend on various factors, for example, the impinging velocity of the droplet to the surface roughness/structure, material, and droplet species. ,, According to Bouillant et al, it was observed that some vortices that are expected to induce mixing occur within the Leidenfrost droplet. In addition, it is considered that the temperature within the droplet is uniform and approximately saturated, owing to excellent mixing.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the droplet rises above its vapor cushion, which acts as a thermal insulator. Therefore, the droplet exists on the superheated surface for more than 300 s without instantaneous evaporation, which is well-known as the Leidenfrost effect. , The Leidenfrost temperature above which the droplet begins to levitate and droplet dynamics depend on various factors, for example, the impinging velocity of the droplet to the surface roughness/structure, material, and droplet species. ,, According to Bouillant et al, it was observed that some vortices that are expected to induce mixing occur within the Leidenfrost droplet. In addition, it is considered that the temperature within the droplet is uniform and approximately saturated, owing to excellent mixing.…”
Section: Introductionmentioning
confidence: 99%